Clinical role of lung clearance index in the assessment of cystic fibrosis lung disease - Armstrong, David K. (The University of Edinburgh, 2019)
[No Deposit Agreement]
The clinical role of lung clearance index in the assessment of cystic fibrosis lung disease
Keywords: lung clearance index; cystic fibrosis; lung disease; cystic fibrosis lung disease; Multiple Breath Washout; early small airways disease; SF6MBW derived LCI; CF lung disease